2020
DOI: 10.4103/psychiatry.indianjpsychiatry_1044_20
|View full text |Cite
|
Sign up to set email alerts
|

Organization of mental healthcare in Bosnia and Herzegovina during coronavirus disease 2019 pandemic

Abstract: Background: Coronavirus disease 2019 (COVID-19), like any other pandemic, has imposed an unprecedented threat to physical and mental health to all nations, worldwide. There is no enough evidence in the literature in this area. The present study has been done to explore the organization of psychiatric services in Bosnia and Herzegovina (BH) to meet mental health needs of BH citizens during the particular restrictive measures caused by COVID-19 pandemic. Materials This on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In addition to COVID-19’s serious consequences for an individual’s physical health, it is important to understand the virus’s consequences for mental health. As the world grapples with this major crisis, the relative risk of infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the risk of mental health impairment associated with infection control need to be identified and weighed [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to COVID-19’s serious consequences for an individual’s physical health, it is important to understand the virus’s consequences for mental health. As the world grapples with this major crisis, the relative risk of infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the risk of mental health impairment associated with infection control need to be identified and weighed [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…After a relatively stable trend in the number of COVID-19 cases throughout the second half of August and September 2020, the situation quickly and dramatically deteriorated, with an exponential rise in the number of cases in mid-October [ 5 ]. To prevent transmission of the disease among patients and hospital staff, work was reorganized during the COVID-19 pandemic, based on guidelines from leadership about the crisis [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24-hour care facilities introduced isolation of residents, the prohibition of visits, or residents leaving the premises. There was the requirement for direct protective measures, and educational activities were undertaken (Bradley, 2020; Mills et al, 2020; Pajević et al, 2020; Quidley-Rodriguez and de Tantillo, 2020; Zingale et al, 2020). Institution staff experienced increased personal risk, which also translates into concern for the welfare of their loved ones and negative emotional experiences (Thompson and Nygren, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In one such study, Marijanović, Kraljević M et al identified an impact on depression, anxiety, and stress levels of oncology staff in five institutions across the country (4). Pajević and colleagues found that several psychiatric institutions across the country ran at a reduced capacity (5).…”
mentioning
confidence: 99%